Effets antimicrobiens des extraits et des huiles essentielles de feuilles de sauge (Salvia officinalis) sur certains germes pathogènes - BEKADA, Mohammed Aness (My University, 2021)
Pathogenic microorganisms constantly represent a danger within public health, in particular because of their resistance to antibiotics, faced with this complication, researchers are trying to explore new avenues to remedy this problem, among the measures that are taken to face it is by introducing the antimicrobial activity of medicinal plants, and it is with this in mind that we have looked into the study of the antimicrobial activity of extracts and essential oils derived from sage leaves (Salvia officinalis), the antimicrobial activity of extracts and essential oils has been evaluated against several bacterial and fungal strains, Regarding Salvia officinalis extracts these have shown potent antimicrobial activity which inhibits the growth of several microbial populations more particularly against S. aureus, B. subtilis, E. coli and Salmonella Enteritidis, similarly me for essential oils which have revealed an effective bactericidal and fungicidal action against B. cereus, B. megatherium, B. subtilis, A. hydrophila, A. sobria and K. oxytoca but have been shown to be less effective against E. coli and S. aureus. Thus the effects of natural substances extracted from medicinal plants could well address the problem of resistance of germs to antibiotics.
Keywords: Salvia officinalis L, antimicrobial activity, extracts, essential oils